Evaluasi Efisiensi Perangkat Base Station Menggunakan Drive Test Pada Antena Single-Band dan Multi-Band - Adith Ismail Shaleh (Jurnal Jaringan Telekomunikasi, 2016)
Telecommunications support equipment and systems play a vital role in the network. Multi-band sectoral antennas are starting to replace single-band sectoral antennas at several base stations. The use of a single-band antenna that requires many antennas at the base station is not practical. The following research is conducting tests to evaluate the coverage area, rx signal level and network throughput produced by a multi-band sectoral antenna. Comparison of coverage area calculation using the walfisch-ikegami method. Testing the coverage area with the rx signal level utilizes a drive test so that the optimization of the success of the multi-band antenna is paired to obtain data to support decision making and determine the efficiency of the device in urban areas. From the test results of these 3 factors, the network efficiency generated by multi-band sectoral antennas and single-band sectoral antennas on the antenna coverage area shows that the results of single-band antennas are further than multi-band antennas. Meanwhile, on the signal side that is measured in the drive test process, the 2G network produced by the multi band antenna is better, for the 3G network the single band antenna is better. The 3G network throughput measurement data shows that the uplink access speed results are not good, because the good throughput value is only 42.54%. Measurements on the downlink side are also in poor condition, because the good throughput value is 38.57%.